Effects of creatine monohydrate supplementation on body composition and strength indices in experienced resistance trained women - Ferguson, T. B.; Syrotuik, D. G. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to examine 10 weeks of creatine monohydrate (Cr) supplementation coupled with resistance training on body composition and strength in women trainees. Twenty-six subjects ingested Cr (n = 13) or a placebo (Pl) (n = 13) at a dose of 0.3 g/kg and 0.03 g/kg body mass for the initial 7 days and subsequent 9 weeks, respectively, while performing a resistance training program 4 days per week. Significant increases (p < 0.05) occurred in both groups for lean body mass and 1 repetition maximum (1RM) bench press and incline leg press. There was a significant main effect for training, but there was no significant difference in the total number of repetitions completed after 5 sets of multiple repetitions to exhaustion at 70% of 1RM for bench press and incline leg press for both groups or in the ability to perform a greater training volume (sets x repetitions x load) in the Cr vs. Pl groups over the 10 weeks. The results indicate that Cr supplementation combined with 10 weeks of concurrent resistance training may not improve strength or lean body mass greater than training only. These findings may be a result of nonresponders due to gender differences or a varying biological potential to uptake Cr within the muscle.